"Eine ungeheure Epopöe unseres eigenen": Language and the Hebrew Bible in Rudolf Borchardt's Das Buch Joram. Issue 1 (2nd January 2019) - Nester, Adi
Abstract : This essay discusses Rudolf Borchardt's theory of language and translation as it is reflected through his early work, the pseudo-biblical poem Das Buch Joram (1905). It argues that the poem, together with Borchardt's writings on translation and his later polemic with Martin Buber on the translation of the Hebrew Bible, articulates a theoretical conception of language as an inherently written and silent entity that dismisses the addressee. It shows further how Buber and Rosenzweig's dialogic understanding of language served Borchardt as a foil, which allowed him to present his own view of language as nationally German in essence.